They didn't know what they got till the crowd was gone - Jan C. van Ours (Tinbergen Institute, 2024)
This paper revisits the relationship between Covid-19-related absence of stadium attendance and match outcomes, analyzing five seasons of the top tier of professional football in the Netherlands. Empty stadiums caused home advantages to disappear completely due to home teams scoring fewer goals. Additionally, in empty stadiums, away teams received fewer yellow cards. This persisted even when stadiums were filled to a maximum of one-third of their capacity. Under these circumstances, there were no effects on team performance. Thus, it is improbable that referee decisions were the intermediary factor influencing team performance. Players of home teams appear to have been directly and adversely affected by the absence of stadium crowds.
Keywords: D91; L83; Z20; 330; Home advantage; professional football; Covid-19